Efektivitas Pembentukan Peraturan Desa Melalui Badan Permusyawaratan Desa Di Kecamatan Bulango Selatan (Universitas Musamus, 2023)
The Village Consultative Body (BPD) as a manifestation of democracy in the administration of village government, accommodates and channels the aspirations of the community. With the existence of BPD, it is hoped that a synergistic relationship will be established between BPD as a representative of the village community and the village head as the head of village government. Because the community has a place to convey aspirations. So that the interests of the people can be accommodated in the formulation of village regulations. However, some functions and tasks of the Village Consultative Body (BPD) have not been implemented properly or even in accordance with established procedures. The method in this study is a method that combines elements of normative law supported by the addition of empirical data. The results showed that the process of planning, formulating and determining the formation of Village Regulations in South Bulango sub-district carried out by BPD and the Village Government process/stages was not in accordance with the provisions of Permendagri 110 of 2016 concerning Village Consultative Bodies and Permendagri 111 of 2014 concerning technical guidelines for regulations in villages. The process carried out by BPD seems to be effective only at the stage of its determination without regard to the makenism that has been arranged so that the hope of promoting good governance has not been fully effective. Thus, strategic policies are needed for the implementation of good government, such as providing technical guidance, increasing the level of formal education, procuring infrastructure facilities and supporting operations for BPD to carry out its functions and roles in the implementation of village government